The synthetic synergistic cinnamon oil CIN-102 is active against Madurella mycetomatis, the most common causative agent of mycetoma. - Mickey Konings; Kimberly Eadie; Wilson Lim; Ahmed H Fahal; Johan Mouton; Nicolas Tesse; Wendy W J van de Sande (PLoS Neglected Tropical Diseases)
Mycetoma is a devastating neglected tropical infection of the subcutaneous tissue and most commonly caused by the fungus Madurella mycetomatis. Treatment of mycetoma consists of a combination of a long term antifungal treatment with itraconazole and surgery. However, treatment is associated with low success rates. Therefore, there is a need to identify novel treatments for mycetoma. CIN-102 is a synthetic partial copy of cinnamon oils with activity against many pathogenic bacteria and fungi. In this study we determined the in vitro activity of CIN-102 against 21 M. mycetomatis isolates and its in vivo efficacy in a M. mycetomatis infected Galleria mellonella larval model. In vitro, CIN-102 was active against M. mycetomatis with MICs ranging from 32 μg/mL to 512 μg/mL. 128 μg/mL was needed to inhibit the growth in 50% of tested isolates. In vivo, concentrations below the MIC of 40 mg/kg and 80 mg/kg CIN-102 prolonged larval survival, but higher concentrations of CIN-102 did not.